2004
DOI: 10.1194/jlr.m300329-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic shock stimulates de novo synthesis of two cardiolipins in an extreme halophilic archaeon

Abstract: The present report illustrates the response to osmotic stress of an extreme halophilic archaeon, Halorubrum sp., isolated from the saltern ponds of Margherita di Savoia in southern Italy. The hypotonic stress induces relevant changes in the membrane lipid composition: archaeal cardiolipin content markedly increases, whereas phosphatidylglycerol (PG) decreases. Membranes isolated from this archaeon after cell disruption by osmotic shock are highly enriched in archaeal cardiolipin and reveal the presence of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
2
39
1
Order By: Relevance
“…Thus haloarchaea are excellent models to study osmoadaptation over an extreme range of salt concentrations. Several recent studies have identified genes that are differentially expressed at different salt concentrations (Bidle, 2003;Choi et al, 2005;Jäger et al, 2002) or detected de novo synthesis of dimeric lipids upon an osmotic downshift (Lopalco et al, 2004), but the opportunities are clearly underexploited.…”
Section: Halophilic Adaptation Of Organismsmentioning
confidence: 99%
“…Thus haloarchaea are excellent models to study osmoadaptation over an extreme range of salt concentrations. Several recent studies have identified genes that are differentially expressed at different salt concentrations (Bidle, 2003;Choi et al, 2005;Jäger et al, 2002) or detected de novo synthesis of dimeric lipids upon an osmotic downshift (Lopalco et al, 2004), but the opportunities are clearly underexploited.…”
Section: Halophilic Adaptation Of Organismsmentioning
confidence: 99%
“…6A reports the TLC lipid profi le of red membranes and lipid assignments based on data in previous literature and mass spectrometric analysis. Experimental lipid masses obtained by MALDI-TOF/MS analysis correspond well to calculated lipid masses and to those previously obtained by ESI-MS analysis ( 12,13 ). It can be seen that in the MALDI spectra of membrane/matrix pellets most of archaebacterial lipids are represented by their sodium adducts.…”
Section: Lipid Analysis Of Intact Lyophilized Archaebacterial Membranmentioning
confidence: 57%
“…A fragment of the pellet was used for MALDI-TOF/MS analysis. The resulting MALDI-TOF/MS lipid profi le was perfectly superimposable onto the lipid profi le obtained by previous TLC and ESI-MS analysis ( 12,13 ). Fig.…”
Section: Lipid Analysis Of Intact Lyophilized Archaebacterial Membranmentioning
confidence: 69%
See 2 more Smart Citations